Sinus Penetration of a Pulsating Device Versus the Classic Squeeze Bottle in Cadavers Undergoing Sinus Surgery. (January 2017) - Chen, Philip G.; Murphy, Jae; Alloju, Les M.; Boase, Sam; Wormald, Peter-John
Objectives: Nasal irrigation is standard in the management of chronic rhinosinusitis both before and after surgical intervention. Numerous irrigation devices are commercially available. The aim of this study was to compare the efficacy of a handheld pulse irrigation device against the gold standard manual squeeze bottle after endoscopic sinus surgery (ESS). Methods: Five cadaveric specimens were prepared with video visualization ports into each sinus. Endoscopic sinus surgery was performed on each cadaver from minimal to maximal dissection. Sinuses were irrigated with fluorescein solution using both devices following each dissection. The irrigations were video recorded. A blinded independent observer scored each irrigation according to a defined scale. Results: Comparison of the 2 devices using an intraclass correlation coefficient (ICC = 0.39) showed the 2 systems differed. Observation of individual sinuses showed the squeeze bottle consistently provided greater irrigation in the maxillary ( P < .006), frontal ( P < .0001), and sphenoid ( P < .0001) sinuses. Pulse irrigation improved only in the maxillary sinus following ESS. Conclusion: The squeeze bottle consistently demonstrated superior irrigation in both native and operated conditions. Interestingly, saline penetration was not significantly improved after opening of the frontal and sphenoid sinuses. This is likely due to decreased backpressure in the nasal passage after opening the sinus cavities.